Creative professor: In search of the new theatrical dramaturgy. (The Voz a Vos Bulletin, 2021)
Since the last century, theatrical reformers have wondered how they could reinforce the theatrical experience. What elements were essential for the theatrical act. Copeau established that the actor was the center of the theatrical work, but at the same time, he always longed for his theatre the appearance of a new playwright who could elevate the work that he carried out with the actors. What he failed to see was that this playwright who felt he had never appeared was much closer to him than he could ever have imagined.